Colored pervious concrete and preparation process thereof
By using nanohydrated calcium silicate, porous basalt aggregate and internal curing agent in color permeable concrete, the contradiction between strength and water permeability of traditional color permeable concrete is solved, and the strength improvement and water permeability maintenance is achieved, meeting the needs of urban construction.
Patent Information
- Application Number
- CN202411809944.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
AI Technical Summary
There is a contradiction between strength and permeability of traditional colored permeable concrete, resulting in limited promotion and application in more fields.
By adding nano-hydrated calcium silicate and porous basalt aggregate to the concrete formula and adding internal curing agent, the hydration reaction of the cement is optimized, the strength of the concrete is enhanced and good water permeability is maintained.
实现了彩色透水混凝土的强度提升和透水效果的保持,能够更好地满足城市建设的需求。
Smart Images

Figure BDA0005180315690000041 
Figure BDA0005180315690000051 
Figure BDA0005180315690000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete technology, and more specifically, to a colored permeable concrete and a preparation process thereof. Background Art
[0002] Colored permeable concrete is an environmentally friendly building material that has been widely used in urban infrastructure construction in recent years. Colored permeable concrete can not only effectively alleviate urban waterlogging problems, but also beautify the environment. With the acceleration of urbanization, the demand for colored permeable concrete continues to increase, and the improvement of the performance of colored permeable concrete has also become a focus of industry attention. However, traditional colored permeable concrete still has many problems in practical applications, such as the contradiction between permeability and mechanical properties, which limits the promotion and application of colored permeable concrete in more fields.
[0003] In the related technology, there is a colored permeable concrete, which includes the following raw materials: 0.101 parts of admixture, 100 parts of water, 360 parts of cement, 20 parts of color powder, 40 kg of admixture (of which fly ash accounts for 33.3 kg and quartz sand accounts for 6.7 kg), 1300 kg of coarse aggregate, 1.5 kg of polyimide fiber, 1 kg of polytetrafluoroethylene fiber, and 4 kg of silicone emulsion.
[0004] Regarding the above-mentioned related technologies, the inventors believe that although silicone emulsion can play a waterproof role, it will also inhibit the hydration reaction of cement, reduce the cement hydration products, and cause the strength performance of permeable concrete to decrease. Summary of the invention
[0005] In the related art, organosilicon emulsion inhibits the hydration reaction of cement, resulting in a decrease in the strength performance of permeable concrete. In order to improve this defect, the present application provides a colored permeable concrete and a preparation process thereof.
[0006] In a first aspect, the present application provides a colored permeable concrete, which adopts the following technical solution: A colored permeable concrete comprises the following raw material components in parts by weight: 340-375 parts of cement, 20-40 parts of color powder, 35-50 parts of mineral admixture, 25-30 parts of internal curing agent, 0.05-0.35 parts of nano material, 1200-1300 parts of coarse aggregate, 1.8-3.2 parts of fiber material, 2-5 parts of organosilicon emulsion, 3.75-4.25 parts of admixture, and 100-105 parts of water, wherein the nano material comprises nano hydrated calcium silicate, and the coarse aggregate comprises porous basalt aggregate.
[0007] By adopting the above technical solution, the present application adds nano-hydrated calcium silicate to the concrete formula, selects porous basalt aggregate as coarse aggregate, and adds an internal curing agent. In the process of hydration of the permeable concrete of the present application, the hydrated calcium silicate can provide more nucleation sites for the CSH gel, accelerate the nucleation and growth rate of the CSH gel, effectively shorten the induction period of cement hydration, promote the hydration of cement, and overcome the inhibitory effect of organic silicon emulsion on cement hydration. At the same time, the porous basalt aggregate selected by the present application can contact the cement paste more fully, thereby forming more connected pores on the contact surface between the cement paste and the coarse aggregate. In addition, the porous basalt aggregate can also absorb a part of the organic silicon emulsion, reducing the negative impact of the organic silicon emulsion on the cement hydration reaction. Since the porous basalt aggregate will absorb a part of the water, the present application adds an internal curing agent as compensation, so that the cement can undergo hydration reaction when the water is relatively sufficient. Through the combination of the above components, the colored permeable concrete of the present application can achieve good permeability while improving its strength, and can fully meet the actual needs of urban construction.
[0008] Preferably, the nano calcium silicate hydrate is prepared according to the following method: (1) adding a polycarboxylate water reducer to deionized water to obtain a PCE solution for later use; adding calcium nitrate to deionized water to dissolve to obtain a calcium salt solution for later use; adding sodium silicate to deionized water to dissolve to obtain a silicate solution for later use; (2) using a peristaltic pump to add the calcium salt solution and the silicate solution to the PCE solution, and then adding sodium hydroxide to obtain a mixed solution, heating the mixed solution in a water bath and continuously stirring the mixed solution, and after the reaction is completed, standing to wait for precipitation, washing and drying the precipitate to obtain nano-hydrated calcium silicate.
[0009] By adopting the above technical scheme, the present application uses calcium nitrate and sodium nitrate as raw materials, polycarboxylate water-reducing agent as precipitation template and stabilizer, and prepares nano calcium silicate hydrate by coprecipitation. Polycarboxylate water-reducing agent has a good steric hindrance effect, which can hinder the agglomeration of nano calcium silicate hydrate, so that nano calcium silicate hydrate has a good dispersion effect in cement paste, which helps to promote the hydration reaction of cement and improve the strength performance of colored permeable concrete.
[0010] Preferably, in the method for preparing the nano-calcium silicate hydrate, the water bath heating temperature in step (2) is 50-60°C.
[0011] By adopting the above technical scheme, the present application optimizes the water bath heating temperature in the process of preparing nano calcium silicate hydrate. Through the synergistic effect of the above temperature conditions and the polycarboxylate water-reducing agent, the dispersion effect of nano calcium silicate hydrate can be further improved, thereby being able to have a more significant promoting effect on the hydration reaction of cement, which helps to improve the strength of colored permeable concrete.
[0012] Preferably, in the method for preparing the nano-calcium silicate hydrate, the pH value of the mixed solution in step (2) is 11.7-12.2.
[0013] By adopting the above technical solution, the present application optimizes the pH value in the process of preparing nano calcium silicate hydrate, which can improve the dispersion effect of nano calcium silicate hydrate and help improve the strength of colored permeable concrete.
[0014] Preferably, the nanomaterial also includes cellulose nanocrystals.
[0015] By adopting the above technical solution, during the hydration reaction of cement, the hydroxyl groups on the surface of cellulose nanocrystals can be complexed with calcium ions and further react with sulfate ions to form CSH gel. The CSH gel wrapped around the cellulose nanocrystals can form a network structure. This network structure can enhance the bonding between the components and enable the effect of nano-hydrated calcium silicate in promoting cement hydration to be more fully exerted, thereby synergistically improving the strength performance of permeable concrete with nano-hydrated calcium silicate.
[0016] Preferably, the weight ratio of the cellulose nanocrystals to the nano-calcium silicate hydrate is (1.5-2.5):1.
[0017] By adopting the above technical solution, the present application optimizes the dosage range of cellulose nanocrystals, which helps to give full play to the synergistic effect of cellulose nanocrystals and nano-hydrated calcium silicate, and improves the strength performance of permeable concrete.
[0018] Preferably, the internal curing agent comprises pre-wet expanded clay.
[0019] By adopting the above technical solution, pre-wetted expanded clay can continuously release moisture during the hardening process of permeable concrete, alleviating the moisture shortage caused by moisture evaporation and water absorption by porous basalt aggregate, promoting the full hydration of cement, and helping to improve the strength performance of permeable concrete.
[0020] Preferably, the internal curing agent also includes SAP resin.
[0021] By adopting the above technical solution, SAP resin can cooperate with pre-wetted expanded clay to achieve slow water release, which helps to give full play to the internal curing effect of the internal curing agent and helps to improve the strength performance of permeable concrete.
[0022] Preferably, the internal curing agent also includes alkali slag.
[0023] By adopting the above technical solution, the main component of the alkali residue is porous flocculent calcium carbonate, which can cooperate with pre-wetted ceramsite and SAP resin to play an internal curing role. At the same time, the alkali residue also contains a certain amount of chloride ions, which can combine with calcium aluminate hydrate in cement paste to form high-strength calcium chloroaluminate hydrate. Under the synergistic effect of internal curing and calcium chloroaluminate hydrate, the addition of alkali residue can further improve the strength performance of permeable concrete.
[0024] In a second aspect, the present application provides a process for preparing colored permeable concrete, which adopts the following technical solution.
[0025] A preparation process of colored permeable concrete comprises the following steps: (1) Mix cement, color powder, mineral admixture, nano calcium silicate hydrate, coarse aggregate and fiber material to obtain dry material, which is set aside; mix admixture and water to obtain admixture solution, which is set aside; (2) The organosilicon emulsion, the internal curing agent, the dry material and the admixture solution are mixed and stirred to obtain a concrete mixture, and the concrete mixture is put into a mold for curing to obtain a colored permeable concrete.
[0026] By adopting the above technical scheme, the present application first prepares the dry material and the admixture solution separately, and then adds the silicone emulsion and the internal curing agent while mixing the dry material and the admixture, and realizes the preparation of colored permeable concrete through the above components.
[0027] In summary, this application has the following beneficial effects: 1. The present application adds nano calcium silicate hydrate to the concrete formula, selects porous basalt aggregate as coarse aggregate, and adds internal curing agent. Through the combination of the above components, the colored permeable concrete of the present application can achieve good permeability while improving strength, which can fully meet the actual needs of urban construction.
[0028] 2. This application uses calcium nitrate and sodium nitrate as raw materials, polycarboxylate water-reducing agent as precipitation template and stabilizer, and prepares nano calcium silicate hydrate by coprecipitation. The addition of polycarboxylate water-reducing agent makes nano calcium silicate hydrate have a good dispersion effect in cement paste, helps to promote the hydration reaction of cement, and improves the strength performance of colored permeable concrete.
[0029] 3. The present application also defines that the nanomaterial includes cellulose nanocrystals. During the hydration reaction of cement, the hydroxyl groups on the surface of the cellulose nanocrystals can be complexed with calcium ions and further react with sulfate ions to form CSH gel. The CSH gel wrapped around the cellulose nanocrystals can form a network structure. This network structure can enhance the bonding between the components and enable the effect of nano-hydrated calcium silicate in promoting cement hydration to be more fully exerted, thereby synergistically improving the strength performance of permeable concrete with nano-hydrated calcium silicate. DETAILED DESCRIPTION
[0030] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0031] Preparation Example of Nano Calcium Silicate Hydrate The following is an explanation using Preparation Example 1.
[0032] Preparation Example 1 In this preparation example, nano calcium silicate hydrate was prepared according to the following method: (1) adding a polycarboxylate water-reducing agent to deionized water to obtain a PCE solution for later use; adding calcium nitrate to deionized water to dissolve to obtain a calcium salt solution for later use; adding sodium silicate to deionized water to dissolve to obtain a silicate solution for later use; in this step, the molar ratio of calcium nitrate to sodium silicate is 1.2:1, and the amount of the polycarboxylate water-reducing agent used is 1% of the sum of the weights of calcium nitrate and sodium silicate; (2) Using a peristaltic pump, the calcium salt solution and the silicate solution were added to the PCE solution, and then sodium hydroxide was added to adjust the pH to 11.4 to obtain a mixed solution. The mixed solution was heated in a water bath at 45° C. and stirred at a rate of 5000 r / min for 40 min. After the reaction was completed, the mixture was allowed to stand and wait for precipitation. The precipitate was washed and dried to obtain nano-hydrated calcium silicate.
[0033] As shown in Table 1, the difference between Preparation Examples 1-5 is that, in the method for preparing nano-calcium silicate hydrate, the water bath heating temperature in step (2) is different.
[0034] Table 1 Water bath heating temperature in step (2) As shown in Table 2, the difference between Preparation Examples 4-7 is that, in the method for preparing nano-hydrated calcium silicate, the pH value of the mixed solution in step (2) is different.
[0035] Table 2 pH value of the mixed solution in step (2) sample pH Preparation Example 4 11.4 Preparation Example 5 11.7 Preparation Example 6 12.0 Preparation Example 7 12.2 Example
[0036] Examples 1-5 The following description is given by taking Example 1 as an example.
[0037] Example 1 In this embodiment, the cement is P.O42.5 silicate cement, the mineral admixture is F class II fly ash, and the color powder is red iron oxide; the internal curing agent is pre-wetted ceramsite, the water content of the pre-wetted ceramsite is 27.8%, and the average particle size is 3.5 mm; the nanomaterial is the nano-hydrated calcium silicate of Preparation Example 1; the coarse aggregate is porous basalt aggregate, and the 24h water absorption of the porous basalt aggregate is 4.3%, and the stacking porosity is 51.8%; the fiber material is a mixture of polyimide fiber and polytetrafluoroethylene fiber in a weight ratio of 3:2, the average length of the fiber material is 20 mm, the average diameter is 6.5 μm, the effective ingredient content of the silicone emulsion is 30 wt%, the effective ingredients are isobutyl triethoxy silane and polyurethane (weight ratio is 1:1), and the admixture is a polycarboxylic acid water reducer with a water reduction rate of 29%.
[0038] The present embodiment provides a colored permeable concrete, which includes the following raw material components in parts by weight: 340 kg of cement, 20 kg of color powder, 35 kg of mineral admixture, 25 kg of internal curing agent, 0.05 kg of nano material, 1200 kg of coarse aggregate, 1.8 kg of fiber material, 2 kg of silicone emulsion, 3.75 kg of admixture, and 100 kg of water.
[0039] This embodiment provides a process for preparing colored permeable concrete, comprising the following steps: (1) Mix cement, color powder, mineral admixture, nano calcium silicate hydrate, coarse aggregate and fiber material to obtain dry material, which is set aside; mix admixture and water to obtain admixture solution, which is set aside; (2) The organosilicon emulsion, the internal curing agent, the dry material and the admixture solution are mixed and stirred to obtain a concrete mixture, and the concrete mixture is put into a mold for curing to obtain a colored permeable concrete.
[0040] As shown in Table 3, the main difference between Examples 1-5 is that the raw material ratios of the permeable concrete are different.
[0041] Table 3 Raw material ratio of permeable concrete sample Example 1 Example 2 Example 3 Example 4 Example 5 Cement / kg 340 350 355 365 375 Toner / kg 20 25 30 35 40 Mineral admixture / kg 35 40 45 50 50 Internal curing agent / kg 25 26 28 29 30 Nanomaterials / kg 0.05 0.06 0.07 0.08 0.10 Coarse aggregate / kg 1200 1225 1250 1275 1300 Fiber material / kg 1.8 2.1 2.4 2.8 3.2 Silicone emulsion / kg 2 2.5 3 4 5 Additive / kg 3.75 3.90 4.00 4.15 4.25 Water / kg 100 101 102 104 105 Example 5-11 As shown in Table 4, the difference between Examples 5-11 is that the preparation examples of nano-hydrated calcium silicate are different.
[0042] Table 4 Preparation example of nano calcium silicate hydrate sample Preparation Example Example 5 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Example 10 Preparation Example 6 Embodiment 11 Preparation Example 7 Example 12 The difference between this embodiment and embodiment 11 is that the nano material consists of 0.10 kg of nano calcium silicate hydrate and 0.10 kg of cellulose nanocrystals.
[0043] Embodiment 13 The difference between this embodiment and embodiment 12 is that the amount of cellulose nanocrystals used is 0.15 kg.
[0044] Embodiment 14 The difference between this embodiment and embodiment 12 is that the amount of cellulose nanocrystals used is 0.20 kg.
[0045] Embodiment 15 The difference between this embodiment and embodiment 12 is that the amount of cellulose nanocrystals used is 0.25 kg.
[0046] Example 16 The difference between this embodiment and embodiment 15 is that the internal curing agent also includes SAP resin. The weight of the SAP resin is 0.2% of the dry weight of the water-retaining expanded clay. The 24-hour water absorption rate of the SAP resin is 185 g / g. The SAP resin is soaked in water for 24 hours before use, and the weight after soaking is used for weighing.
[0047] Embodiment 17 The difference between this embodiment and embodiment 16 is that the internal curing agent further includes alkali residue, the amount of alkali residue used is 25% of the total weight of the water-retaining ceramsite, and the chloride ion content of the alkali residue is 6.3wt%.
[0048] Comparative Example Comparative Example 1 In this comparative example, the cement is P.O42.5 silicate cement, the admixture is composed of Class F Grade II fly ash and quartz sand with a fineness modulus of 2.7, and the color powder is red iron oxide; the coarse aggregate is composed of 1238 kg of guami stone and 62 kg of 1-2 stone; the average length of the polyimide fiber and the polytetrafluoroethylene fiber are both 20 mm, and the average diameter is 6.5 μm; the active ingredient content of the silicone emulsion is 30 wt%, the active ingredients are isobutyl triethoxy silane and polyurethane (weight ratio is 1:1), and the admixture is a polycarboxylic acid water reducer with a water reduction rate of 29%.
[0049] This comparative example provides a colored permeable concrete, including the following raw materials: 0.101 kg of admixture, 100 kg of water, 360 kg of cement, 20 kg of color powder, 40 kg of admixture (of which fly ash accounts for 33.3 kg and quartz sand accounts for 6.7 kg), 1300 kg of coarse aggregate, 1.5 kg of polyimide fiber, 1 kg of polytetrafluoroethylene fiber, and 4 kg of silicone emulsion.
[0050] This comparative example also provides a method for preparing colored permeable concrete, comprising the following steps: (1) Mix cement, color powder, admixture, coarse aggregate, polyimide fiber and polytetrafluoroethylene fiber to obtain dry material, which is set aside; mix admixture and water to obtain admixture solution, which is set aside; (2) The organosilicon emulsion, dry material and admixture solution are mixed and stirred to obtain a concrete mixture, and the concrete mixture is molded and cured to obtain colored permeable concrete.
[0051] Comparative Example 2 The difference between this comparative example and Example 1 is that the components of the permeable concrete do not include an internal curing agent.
[0052] Comparative Example 3 The difference between this comparative example and Example 1 is that the components of the permeable concrete do not include nano-hydrated calcium silicate.
[0053] Comparative Example 4 The difference between this comparative example and Example 1 is that, on the basis of Example 1, the coarse aggregate is replaced by solid basalt crushed stone with a stacking void ratio of 42.6%.
[0054] Performance testing methods 1. Water permeability The permeability coefficient of the drained concrete was measured by referring to the fixed head method in the appendix of "JC / T 2558-2020 Permeable Concrete", and then the permeability coefficient of Comparative Example 1 was used as a benchmark to calculate the ratio between the permeability coefficient of each embodiment and the comparative example and the permeability coefficient of Comparative Example 1. The ratio was recorded as the relative permeability coefficient. The results are shown in Table 5.
[0055] 2. Strength performance Referring to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 28d compressive strength of the concrete in each embodiment and comparative example was tested, and the compressive strength of Comparative Example 1 was used as a benchmark to calculate the ratio between the compressive strength measured in each embodiment and comparative example and the compressive strength of Comparative Example 1, and the ratio was recorded as relative strength. The results are shown in Table 5.
[0056] Table 5 Test results Combining Examples 1-5 and Comparative Example 1 and Table 5, it can be seen that the strength properties and water permeability measured in Examples 1-5 are better than those in Comparative Example 1. This is because in the process of hydration of the permeable concrete of the present application, hydrated calcium silicate promotes the hydration of cement, overcoming the inhibitory effect of the silicone emulsion on cement hydration. At the same time, the porous basalt aggregate can contact the cement slurry more fully, forming more interconnected pores on the contact surface between the cement slurry and the coarse aggregate. In addition, the porous basalt aggregate can also absorb a portion of the silicone emulsion, reducing the negative impact of the silicone emulsion on the cement hydration reaction. Although the porous basalt aggregate will absorb some water, the internal curing agent added in the present application supplements the water, so that the cement can undergo hydration reaction when the water is relatively sufficient. Through the combination of the above components, the colored permeable concrete of the present application can achieve good water permeability while improving the strength, and can fully meet the actual needs of urban construction.
[0057] Combining Example 1 and Comparative Examples 2-4 with Table 5, it can be seen that when the formula system of permeable concrete lacks at least one of porous basalt aggregate, nano-hydrated calcium silicate, and internal curing agent, it is difficult for permeable concrete to have good strength performance and water permeability at the same time. Although Comparative Example 4 uses solid basalt crushed stone with higher strength as coarse aggregate, the contact area between the coarse aggregate and the cement paste is reduced, and the absorption of the coarse aggregate to the organosilicon emulsion is reduced, so the strength performance of Comparative Example 4 is still slightly poor.
[0058] It can be seen from Examples 5-11 and Table 5 that the strength properties measured in Examples 6-11 are better than those in Example 5. This is because in the method for preparing nano-calcium silicate hydrate, when the water bath heating temperature of step (2) is set to 50-60°C, or the pH value of the mixed solution of step (2) is set to 11.7-12.2, the dispersion effect of the nano-calcium silicate hydrate can be further improved, thereby being able to have a more significant promoting effect on the hydration reaction of cement, thereby helping to improve the strength of colored permeable concrete.
[0059] It can be seen from the combination of Examples 11-15 and Table 5 that the strength properties measured in Examples 12-15 are better than those in Example 11. This is because during the hydration reaction of cement, the hydroxyl groups on the surface of the cellulose nanocrystals can be complexed with calcium ions, and further react with sulfate ions to form CSH gel, and the CSH gel wrapped around the cellulose nanocrystals can form a mesh structure. This mesh structure can enhance the combination between the components, and can make the effect of nano-hydrated calcium silicate promoting cement hydration more fully exerted, thereby synergizing with nano-hydrated calcium silicate to improve the strength properties of permeable concrete. When the weight ratio of cellulose nanocrystals to nano-hydrated calcium silicate is (1.5-2.5): 1, it helps to give full play to the synergistic effect of cellulose nanocrystals and nano-hydrated calcium silicate, and improve the strength properties of permeable concrete.
[0060] Combining Example 15, Example 16 and Table 5, it can be seen that the strength performance measured in Example 16 is better than that in Example 15. This is because the SAP resin can cooperate with the pre-wetted expanded clay to achieve slow water release, which helps to give full play to the internal curing effect of the internal curing agent and helps to improve the strength performance of the permeable concrete.
[0061] Combining Example 16, Example 17 and Table 5, it can be seen that the strength performance measured in Example 17 is better than that in Example 16. This is because the alkali residue can synergistically play an internal curing role with the pre-wetted ceramsite and SAP resin, and the chloride ions in the alkali residue can combine with the calcium aluminate hydrate in the cement paste to form high-strength calcium chloroaluminate hydrate. Under the synergistic effect of the internal curing effect and the calcium chloroaluminate hydrate, the addition of alkali residue can further improve the strength performance of permeable concrete.
[0062] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A colored permeable concrete, characterized in that: The permeable concrete comprises the following raw material components in parts by weight: 340-375 parts of cement, 20-40 parts of color powder, 35-50 parts of mineral admixture, 25-30 parts of internal curing agent, 0.05-0.35 parts of nano material, 1200-1300 parts of coarse aggregate, 1.8-3.2 parts of fiber material, 2-5 parts of organosilicon emulsion, 3.75-4.25 parts of admixture, and 100-105 parts of water, wherein the nano material comprises nano hydrated calcium silicate, and the coarse aggregate comprises porous basalt aggregate.
2. The colored permeable concrete according to claim 1, characterized in that: The nano calcium silicate hydrate is prepared according to the following method: (1) Add polycarboxylate water reducer to deionized water to obtain PCE solution, which is for future use; add calcium nitrate to deionized water and dissolve it to obtain calcium salt solution, which is for future use; add sodium silicate to deionized water and dissolve it to obtain silicate solution, which is for future use; (2) Using a peristaltic pump, the calcium salt solution and the silicate solution are added to the PCE solution, and then sodium hydroxide is added to obtain a mixed solution. The mixed solution is heated in a water bath and continuously stirred. After the reaction is completed, the mixed solution is allowed to stand and wait for precipitation. The precipitate is washed and dried to obtain nano-hydrated calcium silicate.
3. The colored permeable concrete according to claim 2, characterized in that: In the method for preparing the nano-calcium silicate hydrate, the water bath heating temperature in step (2) is 50-60°C.
4. The colored permeable concrete according to claim 3, characterized in that: In the method for preparing the nano-calcium silicate hydrate, the pH value of the mixed solution in step (2) is 11.7-12.
2.
5. The colored permeable concrete according to claim 2, characterized in that: The nanomaterials also include cellulose nanocrystals.
6. The colored permeable concrete according to claim 5, characterized in that: The weight ratio of the cellulose nanocrystals to the nano-calcium silicate hydrate is (1.5-2.5):
1.
7. The colored permeable concrete according to claim 1, characterized in that: The internal curing agent includes pre-wet ceramsite.
8. The colored permeable concrete according to claim 7, characterized in that: The internal curing agent also includes SAP resin.
9. The colored permeable concrete according to claim 8, characterized in that: The internal curing agent also includes alkali residue.
10. The process for preparing colored permeable concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Mix cement, color powder, mineral admixture, nano calcium silicate hydrate, coarse aggregate and fiber material to obtain dry material, which is set aside; mix admixture and water to obtain admixture solution, which is set aside; (2) The organosilicon emulsion, the internal curing agent, the dry material and the admixture solution are mixed and stirred to obtain a concrete mixture, and the concrete mixture is poured into a mold for curing to obtain colored permeable concrete.